PENGUATAN PERSONAL HYGIENE BERBASIS PARTICIPATORY ACTION RESEARCH DI SDN 2 PATUNO WAKATOBI - Nadhifa Zahira; Luluk Fajria Maulida (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2025)
This activity to investigates and get the impact of interactive health education on enhancing personal hygiene attitudes and behaviors among elementary students. Using a Participatory Action Research methodology, the study involved 25 students from grades IV to VI at SDN 2 Patuno in Wakatobi, who were chosen through purposive sampling. The intervention included counseling and direct practice. Evaluations were performed using attitude questionnaires and behavioral observations over four weeks. Results from the One Sample T-Test indicated that students initial attitudes were relatively low (mean = 2.26; p = 0.000). After the intervention, Repeated Measures ANOVA revealed a significant improvement (F = 36.410; p = 0.000). The findings confirm that education through interactive media is effective in promoting personal hygiene. Challenges included time constraints, varying student comprehension, and insufficient follow-up, though teacher support and student enthusiasm positively influenced outcomes. Sustained school, family, and health sector collaboration is essential to reinforce long-term behavior change.